Analisis Etika Sosial Anak-Anak di Desa Talian Kereng pada Era Modern - Muhamad Hapi; M.Naufal Mubarak; Tria Syaumilla; Fitrilawatiningsih Fitrilawatiningsih; Rafiah Sytiawati, Rafiah Sytiawati; Maulidia Hidayati, Maulidia Hidayati; Yuliana Yuliana; Mila Mila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to understand the process of social ethics formation among children in Talian Kereng Village in response to the influence of modernization and technological advancements. The research was conducted through a Community Service Program (KKN) that involved in-depth interviews and direct observations of the social lives of children in the village. The findings reveal that the role of family, community leaders, and religious institutions is crucial in instilling social ethical values in children from an early age. In this village, community leaders and religious figures are still highly respected and seen as role models in preserving traditional values. However, significant challenges arise from technological advancements, particularly the use of social media, which influences the perspectives and behavior of children. Many children are becoming influenced by social media content that does not always align with local norms. Additionally, the lack of parental involvement in upbringing, either due to their busy schedules or limited knowledge of parenting in the digital era, exacerbates this situation. Economic disparities also contribute to differences in children's access to technology, ultimately affecting the extent of their exposure to these influences. This study recommends a comprehensive approach that combines formal education, family roles, and community control over the impact of technology. Furthermore, the reinforcement of religious values and local traditions must be strengthened to address the challenges of modernization. In this way, positive social ethics can continue to be preserved and instilled in the younger generation of Talian Kereng Village